Two functional estrogen response elements are located upstream of the major chicken vitellogenin gene. - Burch, J B (1988)
We used a transient-expression assay to identify two estrogen response elements (EREs) associated with the major chicken vitellogenin gene (VTGII). Each element was characterized by its ability to confer estrogen responsiveness when cloned in either orientation next to a chimeric reporter gene consisting of the herpes simplex virus thymidine kinase promoter and the chloramphenicol acetyl transferase-coding region. Deletion analyses indicated that sequences necessary for the distal ERE resided within the region from -626 to -613 (nucleotide positions relative to the VTGII start site) whereas those necessary for the proximal ERE were within the region from -358 to -335. These distal and proximal elements contain, respectively, a perfect copy and an imperfect copy of the 13-base-pair sequence that is an essential feature of the EREs associated with two frog vitellogenin genes. These chicken VTGII EREs mapped near regions that were restructured at the chromatin level when the endogenous VTGII gene was expressed in the liver in response to estradiol. These data suggest a model for the tissue-specific expression of this estrogen-responsive gene.